Nearly complete mitochondrial genome of Siobla xizangensis Xiao, Huang & Zhou, 1988 (Hymenoptera: Tenthredinidae) and phylogenetic analysis - Xi Luo; Meicai Wei; Gengyun Niu (Mitochondrial DNA. Part B. Resources, 2019)
In this study we review the phylogenetic grouping of the sawfly genus Siobla within the superfamily Tenthredinoidea. Using Next Generation Sequencing (NGS), we describe the complete mitochondrial genome of Siobla xizangensis Xiao, Huang & Zhou, . The assembled mitochondrial genome of S. xizangensis was found to be 15015 bp, with three tRNA genes rearranged compared to the ancestral organization. The overall nucleotide composition was 42.6% for A, 11.4% for C, 7.7% for G and 38.3% for T. The phylogenetic tree based on heterogeneity models of 36 Symphytan and two Apocritan recovered the monophyly of Tenthredinidae, and S. xizangensis was identified as the sister group of Tenthredo.